Anti-reduction energy storage ceramic with high polarization characteristic as well as preparation method and application of anti-reduction energy storage ceramic

By using the PbaLabZrcTidOe+xwt%Sm2O3 structure and grain refinement method, the problem of increased lattice defects in PLZT-based ceramics under reducing atmosphere was solved, achieving synergistic optimization of reduction resistance and polarization characteristics, and improving polarization intensity and energy storage performance.

CN121673048APending Publication Date: 2026-03-17INNER MONGOLIA UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610045442.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-14
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Traditional PLZT-based ceramics are prone to oxygen vacancy escape during sintering in a reducing atmosphere, which leads to an increase in lattice defects, a decrease in insulation resistance, and a severe deterioration in polarization characteristics. Existing modification schemes are difficult to achieve synergistic optimization of reduction resistance and polarization characteristics.

Method used

The structure PbaLabZrcTidOe+xwt%Sm2O3 is adopted, in which Sm ions are uniformly mixed with the matrix components. Some Sm ions occupy the A-site lattice of the perovskite phase, suppressing the volatilization loss of Pb and the generation of oxygen vacancies, forming a two-phase synergistic structure of perovskite phase + pyrochlore phase. The grains are refined through multiple ball milling and secondary pre-firing processes to ensure that the ceramic maintains density and stable polarization performance under a reducing atmosphere.

Benefits of technology

Simultaneous optimization of ceramic's anti-reduction properties, polarization performance, and energy storage density was achieved, with polarization intensity increased to 50~80 mC/cm2, energy storage density >12 J/cm3, and energy storage efficiency >70%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121673048A_ABST
    Figure CN121673048A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramics, in particular to an anti-reduction energy storage ceramic with a high polarization characteristic and a preparation method and application thereof. The general structural formula of the ceramic is PbaLabZrcTidOe + xwt% Sm2O3, wherein a is equal to 0.5 to 1.5, b is equal to 0.01 to 0.1, c is equal to 0.5 to 1.5, d is equal to 0.005 to 0.05, and e is equal to 1.6 to 4.7; 0 lt; xlt; 5; the polarization intensity of the ceramic is larger than 50 mC / cm < 2 >, the effective energy storage density is larger than 12 J / cm < 3 >, the energy storage efficiency is larger than 70%, and synchronous optimization of the reduction resistance, the polarization performance and the energy storage density of the ceramic is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ceramic technology. Specifically, it relates to an anti-reduction energy storage ceramic with high polarization characteristics, its preparation method and application. Background Art

[0002] PLZT (lead lanthanum zirconate titanate) - based ceramics have irreplaceable application value in electronic devices such as pulse capacitors and multilayer ceramic capacitors (MLCCs) due to their unique "antiferroelectric - ferroelectric" phase transition characteristics. Their core performance depends on excellent polarization characteristics and anti-reduction stability. These materials achieve high energy storage density through electric field-induced phase transitions. In practical applications, devices often need to be co-fired with base metal electrodes such as copper and nickel to reduce costs, which requires the ceramics to withstand reduction atmosphere sintering while maintaining good polarization performance. However, traditional PLZT - based ceramics have key technical bottlenecks: on the one hand, their sintering temperature is usually higher than the melting point of base metals, and oxygen vacancy escape easily occurs in the reduction atmosphere, resulting in an increase in lattice defects and a decrease in insulation resistance, seriously deteriorating the polarization characteristics; on the other hand, existing modification schemes are difficult to achieve the coordinated optimization of anti-reduction performance and polarization characteristics.

[0003] Chinese Patent Application CN115894019A discloses a PLZST - based antiferroelectric ceramic. By adding Y2(CO3)3 as an anti-reduction additive and sintering in a reduction atmosphere, an energy storage density of 5 J / cm and an energy storage efficiency of 93% are achieved, meeting the atmosphere matching requirements for co-firing with base metal electrodes. However, the scheme only focuses on the optimization of a single performance (energy storage efficiency), sacrificing polarization intensity in exchange for anti-reduction stability, restricting the further improvement of polarization characteristics. Summary of the Invention

[0004] In the first aspect of the present invention, an anti-reduction energy storage ceramic with high polarization characteristics is provided. The structural general formula of the ceramic is: Pb a La b Zr c Ti d O e +xwt%Sm2O3, where a = 0.5 - 1.5, b = 0.01 - 0.1, c = 0.5 - 1.5, d = 0.005 - 0.05, e = 1.6 - 4.7; 0 < x < 5; the polarization intensity of the ceramic > 50 mC / cm 2 .

[0005] The structural general formula of the ceramic in the present invention is: Pb a La b Zr c Ti d O e+xwt% Sm2O3, where a = 0.5 - 1.5, b = 0.01 - 0.1, c = 0.5 - 1.5, d = 0.005 - 0.05, e = 1.6 - 4.7; 0 < x < 5; the anti-reduction property, polarization performance and energy storage density of the ceramic are optimized synchronously. From the perspective of composition and defect regulation, as a rare earth ion, Sm ions are uniformly mixed with the matrix components at the initial mixing stage of the ceramic. Its ionic radius has good adaptability with Pb ions and La ions. Some Sm ions can occupy the A-site lattice of the perovskite phase, inhibiting the volatilization loss of Pb and the generation of oxygen vacancies under a reducing atmosphere. The reduction of oxygen vacancies avoids lattice distortion and structural loosening, laying a foundation for ceramic densification; meanwhile, excessive Sm2O3 reacts with ZrO2 to form the pyrochlore phase Sm2Zr2O7, forming a two-phase synergistic structure of perovskite matrix phase (grain size 1 - 4mm) + pyrochlore second phase (grain size < 1μm). From the perspective of microstructure optimization, the fine Sm2Zr2O7 second-phase particles can fill the gaps between matrix grains, play a role in grain boundary pinning, hinder the excessive growth of matrix grains, and combined with the multiple ball milling and secondary pre-sintering processes in the disclosure, further refine the grains and reduce pores, enabling the ceramic to maintain a plump and dense microstructure after sintering in a reducing atmosphere. The dense structure not only reduces the leakage current but also strengthens the lattice order, providing a structural support for the directional arrangement of dipoles. At the same time, the improvement of the anti-reduction performance inhibits the relaxation hindrance of oxygen vacancies to polarization, making the antiferroelectric-ferroelectric phase transition characteristics of the matrix perovskite phase more stable; the interfacial polarization effect between the second phase and the matrix is superimposed on the intrinsic polarization of the matrix, significantly enhancing the maximum polarization intensity; and the fine second-phase grains increase the number of grain boundaries, hinder the movement of domain walls, and increase the breakdown electric field. The anti-reduction property, polarization performance and energy storage density are optimized synchronously.

[0006] The polarization intensity of the ceramic is 50 - 80 mC / cm 2 .

[0007] The effective energy storage density of the ceramic > 12 J / cm 3 , and the energy storage efficiency > 70%.

[0008] The value range of x is: 1.5 ≤ x ≤ 3.

[0009] The value range of x is: 1.8 ≤ x ≤ 2.5.

[0010] The preparation raw materials of the ceramic include: Pb₃O₄, La₂O₃, ZrO₂, TiO₂ and Sm₂O₃.

[0011] The preparation raw materials of the ceramic also include a solvent and additives, and the additives include at least one of a dispersant, a binder, a plasticizer, and a homogenizer.

[0012] The solvent includes at least one of toluene, anhydrous ethanol, acetone, ethyl acetate, cyclohexane, ethylene glycol ethyl ether, and N,N-dimethylformamide.

[0013] The plasticizer includes at least one of polyethylene glycol, dibutyl phthalate, dioctyl phthalate, tributyl citrate, dioctyl adipate, epoxidized soybean oil, and dibutyl sebacate.

[0014] The dispersant includes at least one of tributyl phosphate, polycarboxylate ammonium salt, Span 80, Tween 80, sodium hexametaphosphate, and triethanolamine.

[0015] The adhesive includes at least one of polyvinyl butyral resin, polyvinyl alcohol, polymethyl methacrylate, epoxy resin, sodium carboxymethyl cellulose, and polyvinyl acetate.

[0016] The homogenizer includes at least one of cyclohexanone, isophorone, diacetone alcohol, propylene glycol methyl ether acetate, acetylacetone, and methyl isobutyl ketone.

[0017] Optionally, the solvent includes toluene and anhydrous ethanol, wherein the mass ratio of toluene to anhydrous ethanol is (1~4):1.

[0018] Optionally, the plasticizer includes polyethylene glycol and dibutyl phthalate; the mass ratio of polyethylene glycol to dibutyl phthalate is (1~2):1.

[0019] Optionally, the dispersant includes tributyl phosphate.

[0020] Optionally, the adhesive may include polyvinyl butyral resin.

[0021] Optionally, the homogenizer includes cyclohexanone.

[0022] The second aspect of this invention provides a method for preparing ceramics, comprising the following steps: preparing Pb3O4, La2O3, ZrO2, TiO2, and Sm2O3 according to the stoichiometric ratio of the general formula for ceramic structure; ball milling and mixing Pb3O4, La2O3, ZrO2, TiO2, and Sm2O3 uniformly, drying, pre-sintering, and ball milling again to obtain powder; ball milling and mixing the powder with solvent and additives to form a casting slurry, and obtaining a casting film through a casting process, and obtaining a ceramic green body through lamination and pressing; and after removing the binder from the ceramic green body, sintering it in a reducing atmosphere to obtain ceramics.

[0023] The thickness of the cast film is 15~40μm.

[0024] The pre-sintering treatment adopts secondary pre-sintering. The temperature of the secondary pre-sintering is 700-900 °C, the heating rate is 1-8 °C / min, the cooling rate is 3-15 °C / min, and the heat preservation time is 2-5 h.

[0025] Optionally, the temperature of the secondary pre-sintering is 800-900 °C, the heating rate is 1-4 °C / min, the cooling rate is 8-15 °C / min, and the heat preservation time is 3-4 h.

[0026] The temperature of the debinding is 450 °C - 700 °C, the heating rate is 0.5-3 °C / min, the cooling rate is 3-5 °C / min, and the heat preservation is 3-5 h.

[0027] Optionally, the temperature of the debinding is 500 °C - 600 °C, the heating rate is 1-3 °C / min, the cooling rate is 3-5 °C / min, and the heat preservation is 4-5 h.

[0028] The reducing atmosphere includes nitrogen and hydrogen. The volume ratio of nitrogen to hydrogen is 200:(0.5-3); the temperature of the buried sintering is 1000-1200 °C, the heating rate is 3-8 °C / min, the cooling rate is 3-10 °C / min, and the heat preservation time is 3-5 h.

[0029] Optionally, the buried sintering method includes sintering in the lead-containing powder.

[0030] Optionally, the volume ratio of nitrogen to hydrogen is 200:(0.5-2); the temperature of the buried sintering is 1100-1200 °C, the heating rate is 3-8 °C / min, the cooling rate is 3-10 °C / min, and the heat preservation time is 3-4 h.

[0031] The third aspect of the present invention provides an application of a ceramic, which is applied to the manufacture of a dielectric energy storage capacitor.

[0032] Beneficial effects 1. The structural general formula of the ceramic of the present invention is: Pb a La b Zr c Ti d O e +xwt%Sm2O3, where a = 0.5-1.5, b = 0.01-0.1, c = 0.5-1.5, d = 0.005-0.05, e = 1.6-4.7; 0 < x < 5; realizing the synchronous optimization of the anti-reduction property, polarization performance and energy storage density of the ceramic.

[0033] 2. By limiting the value range of x in the structural general formula of the ceramic to: 1.5 ≤ x ≤ 3, the polarization intensity of the ceramic can be > 50 mC / cm 2 .

[0034] 3. By limiting the value of x in the general formula of the ceramic structure to the range of 1.8 ≤ x ≤ 2.5, the polarization intensity of the ceramic can be > 70 mC / cm. 2 .

[0035] 4. The ceramic of this invention has low material cost, simple preparation method, and is suitable for industrial production.

[0036] 5. The effective energy storage density of the ceramic of this invention is >12 J / cm³. 3 Energy storage efficiency >70%. Attached Figure Description

[0037] Figure 1 X-ray diffraction patterns of the ceramics prepared for comparison and examples.

[0038] Figure 2 The images show scanning electron microscope (SEM) images of the ceramics prepared for the comparative examples and the examples, as well as the energy dispersive spectroscopy (EDS) spectrum of the surface of Comparative Example 2 (lower right, where PLZT in the EDS spectrum refers to the phase composed of Pb, La, Zr and Ti; Sm refers to the phase region composed of Sm).

[0039] Figure 3 Hysteresis loop diagrams of ceramics prepared for comparison with those of the examples.

[0040] Figure 4 The diagram shows the energy storage performance of the ceramics prepared for comparison with those of the examples. Detailed Implementation

[0041] Example 1 A reduction-resistant energy storage ceramic with high polarization properties, the general formula of which is Pb. 0.94 La 0.04 Zr 0.99 Ti 0.01 O3+1.5wt%Sm2O3.

[0042] A method for preparing a reduction-resistant energy storage ceramic with high polarization characteristics comprises the following steps: (1) Powders were prepared in stoichiometric ratio. The molar ratio of Pb3O4, La2O3, ZrO2 and TiO2 powders was 1.455:0.088:4.379:0.044. After preparation, Sm2O3 was weighed according to the mass ratio of the obtained powders. The mass ratio was 1.5wt%.

[0043] (2) The powder prepared in step (1) is initially mixed by wet ball milling for 24 hours. After the components are fully mixed, dried and ground, it is compacted in a crucible and pre-fired using a two-stage pre-fired method. The pre-fired temperature is raised to 850℃, and then cooled to 800℃ at a cooling rate of 10℃ / min and kept at that temperature for 3 hours before cooling to room temperature.

[0044] (3) Grind and ball mill the pre-calcined block obtained in step (2), dry and grind it through a 200-mesh sieve to obtain powder. Prepare the powder according to the casting slurry formula (by weight): 48% solvent (toluene: anhydrous ethanol = 3:1), 2% dispersant (tributyl phosphate), 4% plasticizer (polyethylene glycol: dibutyl phthalate mass ratio = 1:1, of which polyethylene glycol: Shanghai Chemical Reagent Co., Ltd.), 6% binder (polyvinyl butyral, Sinopharm Chemical Reagent Co., Ltd.), 2% homogenizer (cyclohexanone), and make up the balance with powder. After ball milling for 12 hours, cast film with a thickness of 20 μm is obtained.

[0045] (4) Cut the cast film obtained in step (3) and stack it by 1 mm. Then press it by pressing machine and cold isostatic press to obtain ceramic green body; remove the glue from the ceramic green body and sinter at 550℃ for 5 hours.

[0046] (5) The sample obtained in step (4) is buried and sintered in a reducing atmosphere. The volume ratio of reducing gas nitrogen to hydrogen is 200:1, the sintering temperature is 1180℃, and the temperature is held for 3h. It is recorded as PLZT1.5S ceramic.

[0047] Example 2 A reduction-resistant energy storage ceramic with high polarization properties, the general formula of which is Pb. 0.94 La 0.04 Zr 0.99 Ti 0.01 O3+2wt%Sm2O3.

[0048] A method for preparing a reduction-resistant energy storage ceramic with high polarization characteristics comprises the following steps: (1) Powders were prepared in stoichiometric ratio. The molar ratio of Pb3O4, La2O3, ZrO2 and TiO2 powders was 1.455:0.088:4.379:0.044. After preparation, Sm2O3 was weighed according to the mass ratio of the obtained powders, and the mass ratio was 2wt%.

[0049] (2) The powder prepared in step (1) is initially mixed by wet ball milling for 24 hours. After the components are fully mixed, dried and ground, it is compacted in a crucible and pre-fired using a two-stage pre-fired method. The pre-fired temperature is raised to 850℃, and then cooled to 800℃ at a cooling rate of 10℃ / min and kept at that temperature for 3 hours before cooling to room temperature.

[0050] (3) Grind the pre-fired block obtained in step (2) and ball mill it to refine it. Dry and grind it through a 200-mesh sieve to obtain powder. Prepare it according to the casting slurry formula (same as in Example 1). After ball milling for 12 hours, perform casting process to obtain a 20μm thick casting film.

[0051] (4) Cut the cast film obtained in step (3) and stack it by 1 mm. Then press it by pressing machine and cold isostatic press to obtain ceramic green body; remove the glue from the ceramic green body and sinter at 550℃ for 5 hours.

[0052] (5) The sample obtained in step (4) is buried and sintered in a reducing atmosphere. The volume ratio of reducing gas nitrogen to hydrogen is 200:1, the sintering temperature is 1160℃, and the temperature is held for 3h.

[0053] Example 3 A reduction-resistant energy storage ceramic with high polarization properties, the general formula of which is Pb. 0.94 La 0.04 Zr 0.99 Ti 0.01 O3+3wt%Sm2O3.

[0054] A method for preparing a reduction-resistant energy storage ceramic with high polarization characteristics comprises the following steps: (1) Powders were prepared in stoichiometric ratio. The molar ratio of Pb3O4, La2O3, ZrO2 and TiO2 powders was 1.455:0.088:4.379:0.044. After preparation, Sm2O3 was weighed according to the mass ratio of the obtained powders. The mass ratio was 3wt%.

[0055] (2) The powder prepared in step (1) is initially mixed by wet ball milling for 24 hours. After the components are fully mixed, dried and ground, it is compacted in a crucible and pre-fired using a two-stage pre-fired method. The pre-fired temperature is raised to 850℃, and then cooled to 800℃ at a cooling rate of 10℃ / min and kept at that temperature for 3 hours before cooling to room temperature.

[0056] (3) Grind the pre-fired block obtained in step (2) and ball mill it to refine it. Dry and grind it through a 200-mesh sieve to obtain powder. Prepare it according to the casting slurry formula (same as in Example 1). After ball milling for 12 hours, perform casting process to obtain a 20μm thick casting film.

[0057] (4) Cut the cast film obtained in step (3) and stack it by 1 mm. Then press it by pressing machine and cold isostatic press to obtain ceramic green body; remove the glue from the ceramic green body and sinter at 550℃ for 5 hours.

[0058] (5) The sample obtained in step (4) is buried and sintered in a reducing atmosphere. The volume ratio of reducing gas nitrogen to hydrogen is 200:1, the sintering temperature is 1200℃, and the temperature is held for 3h.

[0059] Comparative Example 1 A type of ceramic with the general structural formula: Pb0.94 La 0.04 Zr 0.99 Ti 0.01 O3, the ceramic preparation method includes the following steps: (1) Powders were prepared in stoichiometric ratios, with the molar ratio of Pb3O4, La2O3, ZrO2 and TiO2 powders being 1.455:0.088:4.379:0.044.

[0060] (2) The powder prepared in step (1) is initially mixed by wet ball milling for 24 hours. After the components are fully mixed, dried and ground, it is compacted in a crucible and pre-fired using a two-stage pre-fired method. The pre-fired temperature is raised to 850℃, and then cooled to 800℃ at a cooling rate of 10℃ / min and kept at that temperature for 3 hours before cooling to room temperature.

[0061] (3) Grind the pre-fired block obtained in step (2) and ball mill it to refine it. Dry and grind it through a 200-mesh sieve to obtain powder. Prepare it according to the casting slurry formula (same as in Example 1). After ball milling for 12 hours, perform casting process to obtain a 20μm thick casting film.

[0062] (4) Cut the cast film obtained in step (3) and stack it by 1 mm. Then press it by pressing machine and cold isostatic press to obtain ceramic green body; remove the glue from the ceramic green body and sinter at 550℃ for 5 hours.

[0063] (5) The sample obtained in step (4) is buried and sintered in a reducing atmosphere. The volume ratio of reducing gas nitrogen to hydrogen is 200:1, the sintering temperature is 1160℃, and the temperature is held for 3h.

[0064] Comparative Example 2 A type of ceramic with the general structural formula: Pb 0.94 La 0.04 Zr 0.99 Ti 0.01 O3+5wt%Sm2O3.

[0065] The ceramic preparation method comprises the following steps: (1) Powders were prepared in stoichiometric ratio. The molar ratio of Pb3O4, La2O3, ZrO2 and TiO2 powders was 1.455:0.088:4.379:0.044. After preparation, Sm2O3 was weighed according to the mass ratio of the obtained powders. The mass ratio was 5wt%.

[0066] (2) The powder prepared in step (1) is initially mixed by wet ball milling for 24 hours. After the components are fully mixed, dried and ground, it is compacted in a crucible and pre-fired using a two-stage pre-fired method. The pre-fired temperature is raised to 850℃, and then cooled to 800℃ at a cooling rate of 10℃ / min and kept at that temperature for 3 hours before cooling to room temperature.

[0067] (3) Grind the pre-fired block obtained in step (2) and ball mill it to refine it. Dry and grind it through a 200-mesh sieve to obtain powder. Prepare it according to the casting slurry formula (same as in Example 1). After ball milling for 12 hours, perform casting process to obtain a 20μm thick casting film.

[0068] (4) Cut the cast film obtained in step (3) and stack it by 1 mm. Then press it by pressing machine and cold isostatic press to obtain ceramic green body; remove the glue from the ceramic green body and sinter at 550℃ for 5 hours.

[0069] (5) The sample obtained in step (4) is buried and sintered in a reducing atmosphere. The volume ratio of reducing gas nitrogen to hydrogen is 200:1, the sintering temperature is 1200℃, and the temperature is held for 3h.

[0070] Performance testing methods and data The ceramics prepared in the examples and comparative examples were subjected to performance tests.

[0071] 1. X-ray diffraction: such as Figure 1 As can be seen from the comparison with the PDF (#97-015-6137) card, Sm2Zr2O7 has been successfully synthesized. At the same time, the diffraction peaks of the comparative example and the example all show a pure perovskite structure. The coexistence of two phases can be clearly seen in comparative example 2, example 2, and example 3. The great improvement in the effective energy storage density of example 2 can be attributed to the result of the synergistic mixing of two phases in an appropriate ratio. At the same time, the diffraction peaks remain stable under a reducing atmosphere, indicating that sintering under a reducing atmosphere does not change the crystal structure of the ceramic.

[0072] 2. Surface scanning electron microscopy: from Figure 2 As can be seen from the data, all samples have a clear grain structure. Compared with Examples 1 and 3, the grains in Example 2 are full and densely packed. The addition of Sm2O3 helps to improve the densification of the ceramic body. At the same time, the aggregation of Sm elements can be clearly seen in the energy spectrum, indicating the existence of the second phase. This shows that the ceramic still has a dense structure under the sintering conditions of reducing atmosphere and that the second phase was successfully synthesized.

[0073] 3. Breakdown electric field and polarization intensity: Au (gold) electrodes were formed on the upper and lower surfaces of the sample by ion sputtering to test its performance (using the ferroelectric integrated testing system from Radiant Corporation, USA), with an electrode diameter of 1 mm; the hysteresis loop of the material was tested using the ferroelectric integrated testing system. Figure 3 The test frequency was 10 Hz. The polarization intensity under different electric fields was obtained from the hysteresis loop results. Eight samples were tested, and the average value was used to obtain the final polarization intensity. The breakdown electric field of the eight samples was calculated using the Weber distribution to obtain the material's breakdown electric field. The energy storage density and efficiency were calculated using the hysteresis loop. Figure 4 The energy storage density, polarization intensity, and efficiency data are listed in Table 1. The test data for energy storage density and efficiency are shown in Table 3. The obtained test data for energy storage density, polarization intensity, and efficiency are summarized in Table 1. From Table 1 and... Figure 3 As can be seen, with the addition of Sm2O3, the breakdown electric field of Example 2 is slightly increased, and the comparative example has the same hysteresis loop characteristics as the examples. The breakdown electric field of Comparative Example 1 is 320 kV / cm, and the polarization intensity is 39 mC / cm. 2 Example 2: The breakdown electric field is 500 kV / cm, and the maximum polarization intensity is 71 mC / cm. 2 This indicates that under sintering conditions in a reducing atmosphere, the breakdown electric field and maximum polarization intensity of the PLZT ceramic body are still improved, suggesting that the addition of Sm2O3 improves the reduction resistance and effective energy storage density of the ceramic body.

[0074] Table 1

[0075] 4. Energy storage density and energy storage efficiency test: The data are obtained from calculations and are listed in Table 1 and... Figure 4 The calculation formula is as follows:

[0076]

[0077]

[0078] In the formula, W tot , W rec , h , E , P r , P max These are energy storage density, recyclable energy storage density, energy efficiency, applied electric field, residual polarization, and maximum polarization intensity, respectively.

[0079] from Figure 4 It can be seen that the appropriate addition of Sm2O3 is beneficial to obtaining extremely high energy storage density. The recoverable energy storage density of Example 2 is 17.81 J / cm³. 3The energy storage efficiency is 77%, indicating that when 2wt% Sm2O3 is added, lead-based energy storage ceramics can still achieve extremely high energy storage density during sintering in a reducing atmosphere, and the resistance to reduction is significantly improved.

Claims

1. A reduction-resistant energy storage ceramic with high polarization characteristics, characterized in that, The structural general formula of the ceramic is: Pb a La b Zr c Ti d O e +xwt%Sm2O3, where a = 0.5~1.5, b = 0.01~0.1, c = 0.5~1.5, d = 0.005~0.05, e = 1.6~4.7; 0 < x < 5; The polarization intensity obtained by testing the ceramic using the ferroelectric comprehensive test system of Radiant Company in the United States with an electrode diameter of 1 mm and a test frequency of 10 Hz is > 50 mC / cm 2 .

2. The ceramic according to claim 1, characterized in that, The polarization intensity of the ceramic is 50~80 mC / cm. 2 .

3. The ceramic according to claim 2, characterized in that, The effective energy storage density of the ceramic is >12 J / cm³ 3 Energy storage efficiency >70%.

4. The ceramic according to claim 3, characterized in that, The range of x is: 1.5≤x≤3.

5. The ceramic according to claim 4, characterized in that, The range of x is: 1.8≤x≤2.

5.

6. The ceramic according to claim 1, characterized in that, The raw materials for preparing the ceramic include: Pb3O4, La2O3, ZrO2, TiO2 and Sm2O3.

7. The ceramic according to claim 6, characterized in that, The raw materials for preparing the ceramic also include solvents and additives, wherein the additives include at least one of dispersants, binders, plasticizers, and homogenizers.

8. A method for preparing ceramics according to claim 7, characterized in that, Includes the following steps: Pb3O4, La2O3, ZrO2, TiO2, and Sm2O3 were prepared according to the stoichiometric ratio of the general formula for ceramic structure. The Pb3O4, La2O3, ZrO2, TiO2, and Sm2O3 were ball-milled until homogeneous, dried, pre-sintered, and then ball-milled again to obtain powder. The powder was ball-milled with solvent and additives to form a casting slurry, and a casting film was prepared through a casting process. The film was then laminated and pressed to obtain a ceramic green body. After removing the binder, the ceramic green body was sintered in a reducing atmosphere to obtain the ceramic.

9. The method for preparing ceramics according to claim 8, characterized in that, The thickness of the cast film is 15~40μm.

10. An application of the ceramic according to any one of claims 1-7, characterized in that, It is used in the manufacture of dielectric energy storage capacitors.

Citation Information

Patent Citations

  • Anti-ferroelectric ceramic material and low-temperature sintering preparation method thereof

    CN115894019A